The petrogenesis of carbonatites: mineral variations and effects on the REE mineralization - Giebel, Robert Johannes (University of the Free State, 2019)
Carbonatites have high economic potential and are important sources for a range of commodities, including P, Fe, F, Cu, high field strength elements (HFSE, e.g., Zr, Hf, Nb, U), and especially the rareearth elements (REE). About 10% of all known carbonatite occurrences (50 out of 550) are currently mined for those commodities and about 40% of all REE exploration projects target carbonatites and associated rock types. Despite their economic importance we have a limited understanding of carbonatite systems and their relationship with associated rock types. A range of processes result in strong variability in the mineralogy and mineral chemistry of carbonatites, and hence their economic viability. However, scientific interest in understanding the complex mineralizations and associations in carbonatitic systems has tremendously increased. Our studies focused on two carbonatite complexes, namely the Palabora Carbonatite Complex (South Africa) and the Kaiserstuhl Volcanic Complex (Germany), that display a variety of mineral assemblages and mineral chemistries. The Palabora carbonatite clearly indicates an insignificant orthomagmatic REE mineralization, a late-magmatic enrichment of REE mineral phases and an effective post-magmatic redistribution of the REE mineralization. The Kaiserstuhl carbonatites, on the other hand, show a greater diversity in their REE concentrations due to a wider range of petrogenetic processes. Some of the Kaiserstuhl carbonatite bodies experienced a strong hydrothermal enrichment of REE. In contrast, one Kaiserstuhl carbonatite body, namely the Badberg, shows strong retention of REE by apatite during early orthomagmatic stages. This carbonatite body lacks a late-magmatic to hydrothermal REE enrichment. The enhanced incorporation of REE into orthomagmatic apatite is attributed to a coupled substitution that is promoted by host rock contamination. Since the REE-hosting mineral type, its abundance and its mineral associations are some geological influences on a carbonatite being economically viable or not, understanding the causes and modifications of REE mineralization is of crucial importance. We use the Palabora complex (and the Fen complex, Norway) to illustrate the individual evolutionary stages of those carbonatites. At the Kaiserstuhl complex we illustrate the influence of external silicate contamination on the economic potential of a carbonatite. Furthermore, we present a new model that reconstructs the emplacement of, and relation between, carbonatites and associated rocks. This model predicts the ratio between carbonatites and associated rock types. It also explains the origin of phoscorite magmas.
Thesis (Ph.D.(Geology))--University of the Free State, 2019
Keywords: The Palabora Carbonatite Complex; The Kaiserstuhl Volcanic Complex; Rare-Earth Elements; Carbonatites; Phoscorites; Mineral variations; Mineralogy and mineral chemistry; Petrogenesis and multi-stage evolution; Hydrothermal and magmatic processes; Emplacement model; Phalaborwa (South Africa); Rare earth metals; Mineralogical chemistry